SUATU TINJAUAN YURIDIS TERHADAP PERJANJIAN EKSTRADISI INDONESIA DAN REPUBLIK KOREA SELATAN - Alma Panjaitan; Jelly Leviza; Deni Purba (Journal of USU International Law, 2013)
Abstraksi Extradition treaty between Republic of Indonesia and Republic of Korea was signed on the 28th November 2000 in Jakarta and ratified through Act Number 42 of 2007. With the ratification of Act Number 42 of 2007 the relationship and cooperation between the two countries for law enforcement and eradication of crimes are mutually beneficial. This study focuses on the history and development of the extradition treaty, procedures to implement the extradition and legal analysis of the extradition treaties of the Republic of Indonesia and the Republic of Korea.Keywords : Extradition, Indonesia, South Korea